Balanced Nutrition and Nutritional Status of Early Childhood: A Descriptive Study at the Integrated Health Post (Posyandu) in Aka-Akae Village, Sidenreng Rappang Regency - Maswati; Nurbaya; Rahayu; Mayani; Nurmiati; Harisma; Sumiati Kadir; Siti Nur Hasanah; Asnadia (Journal of Creative Power and Ambition (JCPA), 2026)
Early childhood is a critical and sensitive golden period for meeting nutritional needs. Balanced nutrition during this phase serves as the primary foundation for optimal physical growth, cognitive development, intelligence, and long-term health. This study aims to analyze the application of balanced nutrition principles in early childhood, identify factors influencing nutritional status, and describe nutritional status development of young children at Posyandu Mattirowali E, Aka-Akae Village, Watang Sidenreng District, Sidenreng Rappang Regency (Sidrap). The research employed a descriptive design with a mixed-method approach (qualitative and quantitative). Data were collected through participant observation, semi-structured in-depth interviews with 7 parents and 2 Posyandu cadres, and anthropometric measurements (weight, height, and head circumference). Data were analyzed using Z-scores based on WHO growth standards for TB/U, BB/U, and BB/TB indicators. Results revealed that all 7 children born in 2023 (100%) fell under the short or very short category based on TB/U. The BB/U indicator showed 57.2% had low or very low weight, while 85.7% showed good nutritional status based on BB/TB. Weight growth trend data for 16 children born in 2024 showed 83.3% gained weight in May 2026, indicating nutritional improvement. Key factors affecting children's nutritional status include maternal knowledge of balanced nutrition, feeding practices, family socioeconomic conditions, access to nutritious food, and infection frequency. Sustained nutrition education through Posyandu and cross-sector support are critical to achieving optimal early childhood growth and health.